Snapshots of the relationship between photo, caption and headline in news articles on food - Saberi, Dariush; Chan, Swee Heng (Universiti Putra Malaysia Press, 2015)
The paper is motivated by investigations on how visuals interplay with text to create meaning. Today in news reporting, written text alone would not suffice to attract the attention of readers. Photos play a major role in depicting a theme and also to create mental representations that would help to bring out the message in the text. The current study focuses on examination of the relationship between photo, caption and headlines as the initial elements of a news article that set the scene for further reading. A qualitative approach is used to analyse the content of the photos as well as the captions and the headlines. Each of the elements is discussed and the elements are then linked together to provide coherence of response to the effects that are created. The analysis also points to the techniques used by news writers in the evocation of emotions and attitude towards a universal concern of food and its critical shortages through the manipulation of the interrelationship between photo, caption and headline.